diagnostic validity of cytology in the detection of neoplastic lesions of the cervix at the National Maternal-Perinatal Institute during 2019 - Samillan Salhuana, Cristopher Jhonatan (2022)
Objective: To determine the diagnostic validity of cytology in the detection of neoplastic lesions of the cervix at the National Maternal-Perinatal Institute during 2019. Materials and Methods: Observational, descriptive, retrospective cross-sectional study. 161 patients who had cervical cytology and histology examinations of the cervix were studied at the INMP during 2019. The information from the medical records with positive and negative results of neoplastic lesions of the cervix was collected through a data collection form. which met the inclusion and exclusion criteria of this study. The SPSS V25.0 program was used for statistical analysis; the Chi-square test was used to calculate the association measures, establishing the level of significance at 5% (p <0.05). Results: cervical cytology obtained a sensitivity of 8.0%, specificity of 64.9%, positive predictive value of 21.2% and negative predictive value of 37.5% compared to histology of the cervix; A statistically significant association was found between cervical cytology and histology of the cervix (p = 0.000). The predominant age group was adult patients with 75.2% of cases, where the average age of positive results was 42.8 (+/- 12.5 years), an association was also found with cervicovaginal cytology, obtaining a value p of 0.016. Conclusions: In our study, although cervical cytology had a low sensitivity and moderate specificity, an association with the histology of the cervix could be found; thus concluding that cytology is a very important tool for the detection of neoplastic lesions of the cervix.